Fatores que afetam a satisfação de pacientes em serviços de saúde :um estudo em setor ambulatorial de hospital - Barbosa, Leonar Tiago (2006)
This thesis shows concepts and models related to customer satisfaction measurement, focusing in detail on patients satisfaction evaluations in a policlinic sector of a hospital located in Natal RN. To reach this aim, two hundred and fifty one patients of this hospital were interviewed. The methodology approach includes a theoretical basis through a review and study of previous research on the topic, governmental initiatives and management systems which deal with excellence and need more reports concerning customers perceptions about satisfaction. Furthermore, it was included some models of nationals index about customer satisfaction. The Norwegian model was used in this thesis. The use of this approache, together with a multiple regression analysis, led to results that shows the factors which affect patients satisfaction in a policlinic sector. They are four as following: The evaluation of physician attendance; its results; simplicity of accessibility when health services are needed; and both support and tranquility given by the hospital. The study results can support researches of a conceptual model to determinate the aspects which affect the patient s satisfaction and could be a contribution to a development of a national costumer satisfaction index